Generics substitution, bioequivalence standards, and oversight of international pharmaceutical producers: Complex issues facing the FDA - Aparna Mathur; Roger Bate (American Enterprise Institute (AEI), 2015)
The rules underlying the assessment of quality of generic drugs, and their bioequivalence to brand name products, have not changed significantly since the passage of the Hatch-Waxman Act in 1984. Yet the products on the market are significantly more complicated today, which may imply that two bioequivalent products are not identical to each other. Providing evidence from medications to treat epilepsy, depression and other serious conditions this paper shows that switching from an innovator brand to a generic may result in adverse consequences for patients. Moreover, the clinical impacts of shifting from one generic to another generic are also unknown. In a self-conducted survey, we provide original data to show that in only 10% of pharmacies surveyed over four consecutive months was the same generic (atorvastatin) available. Hence consumers often have less choice with respect to the generics they buy from brick and mortar pharmacies and we need more information to understand whether this type of enforced generic switching is advisable. Additionally, generic and brand name drugs source more ingredients and even final products from outside the U.S. especially India and China, countries with poor regulatory oversight. This would impact quality in US markets. The most notable failure in this regard was with the Indian firm Ranbaxy. Even after repeated failures to ensure quality at Ranbaxy and other Indian firms, and weak oversight in China, US patients are still prescribed their products. In this paper, we document these complex issues facing the FDA and conclude that transparency as well as updating of bioequivalence standards may be important to overcome some of these challenges. Further, transparency in labelling where products are sourced from could be a first step towards improving patient safety.
Keywords: A; 330; pharmaceuticals; FDA; drug policy; generic drugs